Greener energy for ocean transportation - Neo, Hui Yi (Nanyang Technological University, 2021)
This report aims to study the feasibility of alternative marine fuels. With the increasing focus on environmental sustainability, the maritime industry is not spared as well. As part of the efforts of the industry to achieve decarbonization, an option would be to switch to greener alternative fuels for ocean transportation. Three fuels - LNG, biofuels and hydrogen, would be considered in this study. We would compare its ability in the extent of emissions reduction, economical, technological and regulatory factors, with that of the conventional heavy fuel oils (HFOs), in the form of literature review. Primary research – survey questionnaire and interviews, would be carried out to gather opinions of industry players regarding the decarbonization efforts. Both the primary and secondary research would then be further compared and analysed before. A final evaluation would be given on the possibility of hydrogen being adopted as the new marine fuel, as compared to the other two fuels. This study would then be concluded with an overview of the maritime industry’s efforts in decarbonization. From our findings, we conclude that there remain multiple obstacles before alternative greener fuels could be adopted. The key factors are mainly regulatory frameworks and prices of these fuels. Only with a unified effort globally and cooperation from various stakeholders along the supply chain, would the adoption become commercially available and feasible. Nonetheless, there is also room for more research and development for these fuels to ensure that they become competitively efficient as compared to the conventional Heavy Fuel Oils (HFOs). Taking various factors into consideration, we believe that the adoption of these fuels is feasible. LNG, biofuels and hydrogen are feasible in the short-term, mid-term and long-term respectively.